Eine neue Art von Finanzkrisen in Lateinamerika - Salma, Pierre (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2004)
Finance crisis of the eighties resulted out of the external claims to debtor nations and the problems to get the necessary internal resources. The finance crisis of the nineties are founded in the financial constraints set by the international finance markets. Under this conditions growth of the economy is possible, but in an unstable and risky way.